Educational Finance in Pre-Covid and Covid-19 Era in Nigeria: What has changed and Way Forward - ADESUA, Veronica Olubunmi; BALOGUN, Babatunde Nurudeen; ADELAKUN, Iyanuoluwa Samuel (Journal of Education and Practice, 2021)
For few decades, education has been receiving financial attention from the government and other concerned personnel in the society owing to the general belief that education is the key that opens great door of sustainable development to any country of the world; it is the major tool for individual, national, socio-economic development, poverty eradication and it should be adequately financed to have desired results. Unfortunately education is still underfunded in Nigeria despite enormous resources invested in it in form of allocations yearly. This has over the years exposed the educational sector of Nigeria to drastic ruin as a result of mismanagement of allocated resources and other functional financial fraudulent acts in the sector. Few years back the world experienced global economic meltdown (recession) which also led the Nigerian education sector to struggle with meeting its financial obligations and while the nation was witnessing this, the unexpected outbreak of coronavirus (covid-19) pandemic occurred forcing the sector to experience extremely lack of finance to keep the sector moving. To justify this insinuations this paper reviewed the financing of the educational system in pre-covid and covid-19 era in Nigeria; what has changed over the years, the challenges associated with the changes and the way forward in form of recommendations.